PENGEMBANGAN SISTEM PELAPORAN BENCANA KEBAKARAN PADA DINAS PEMADAM KEBAKARAN - Fernando, Iqbal; Irawan, Agus; Fitriani, Cindy (Journal of Innovation And Future Technology (IFTECH), 2024)
Efficient and timely fire reporting system is a crucial aspect in managing emergency incidents involving fire risks. Currently, many major cities in Indonesia, including Bandung, still face challenges in effectively handling fire reports. Therefore, this research aims to design a fire reporting system using the Waterfall method based on mobile technology, with a case study on the Fire Department (DAMKAR) of Bandung. This study proposes the Waterfall method as a structured and organized framework for system development. The Waterfall method enables sequential development phases, starting from planning, needs analysis, design, implementation, to testing and maintenance. In this research, mobile-based technology is used as a reporting medium, allowing the public to report fires quickly and accurately. The results of this study are expected to contribute to the design of an efficient and responsive fire reporting information technology system. Additionally, the Bandung DAMKAR case study can serve as a reference for similar system development in other cities. Another expected benefit is an improved response and rapid handling of fire reports, thereby minimizing material losses and human casualties. It is hoped that the proposed system will help enhance the performance and effectiveness of DAMKAR Bandung in fire management. Furthermore, the findings of this research are expected to provide new insights to authorities in addressing fire challenges in major cities in Indonesia. Keywords: Information Technology System, Waterfall Method, Fire Reporting, Mobile, DAMKAR, Bandung.